PENGARUH EMPLOYER BRANDING, E-RECRUITMENT, DAN KOMPENSASI TERHADAP MINAT MELAMAR PEKERJAAN PADA LULUSAN FEBM ANGKATAN 2021 UNIVERSITAS MARITIM RAJA ALI HAJI - Emilia Auliani, Suci; Paramita, Bunga; Anggi Fani, Lastri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of employer branding, e-recruitment, and compensation on job application intention among the 2021 graduates of the Faculty of Economics and Maritime Business, Raja Ali Haji Maritime University. This study employed a quantitative approach using a simple random sampling technique involving 106 respondents. The data were analyzed using multiple linear regression with IBM SPSS Statistics 22. The results indicate that employer branding has no significant effect on job application intention, while e-recruitment and compensation have positive and significant effects on job application intention. Simultaneously, employer branding, e-recruitment, and compensation have a significant effect on job application intention, indicating that job application intention is influenced by employer branding, e-recruitment, and compensation.